2013
DOI: 10.1016/j.cub.2013.03.039
|View full text |Cite
|
Sign up to set email alerts
|

NMII Forms a Contractile Transcellular Sarcomeric Network to Regulate Apical Cell Junctions and Tissue Geometry

Abstract: Summary Nonmuscle myosin II (NMII) is thought to be the master integrator of force within epithelial apical junctions, mediating epithelial tissue morphogenesis and tensional homeostasis [1-3]. Mutations in NMII are associated with a number of diseases due to failures in cell-cell adhesion [4-8]. However, the organization and the precise mechanism by which NMII generates and responds to tension along the intercellular junctional line are still not known. We discovered that periodic assemblies of bipolar NMII f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
176
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(199 citation statements)
references
References 30 publications
22
176
1
Order By: Relevance
“…An increase in the peripheral actomyosin tension is also a possibility because vasopressin has been shown to activate myosin light chain kinase (31), which, in turn, activates myosin light chain and hence nonmuscle myosin II activity (55). In the ear's organ of Corti, the nonmuscle myosin IIB and IIC, not IIA, are organized as a sarcomeric network surrounding the apical perimeter of the cells (56). This arrangement was shown to regulate the length of the apical perimeter and the apical surface area.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the peripheral actomyosin tension is also a possibility because vasopressin has been shown to activate myosin light chain kinase (31), which, in turn, activates myosin light chain and hence nonmuscle myosin II activity (55). In the ear's organ of Corti, the nonmuscle myosin IIB and IIC, not IIA, are organized as a sarcomeric network surrounding the apical perimeter of the cells (56). This arrangement was shown to regulate the length of the apical perimeter and the apical surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Myosin activity in these tissues reduces the distance between sarcomeric repeats, consistent with myosin motor activity pulling antiparallel F-actin arrays together, driving a pursestring-like contraction. In adjacent cells, the repeated pattern of myosin and F-actin cross-linking proteins in F-actin bundles is aligned across the junctional interface, suggesting that individual units of this sarcomeric repeat are somehow coordinated and possibly anchored across junctional interfaces (Ebrahim et al, 2013). Cell culture studies have shown that actin-myosin fibers without a clear sarcomere organization can also generate tension around the apical perimeter and can drive apical constriction (Ishiuchi and Takeichi, 2011;Ratheesh et al, 2012;Wu et al, 2014).…”
Section: Contractile Fibersmentioning
confidence: 99%
“…Classic studies of neurulation in embryos and of cultured epithelia suggested that the contraction of circumferential actin-myosin bundles or fibers underlying the adherens junctions causes the cell apex to constrict, analogous to drawing a purse-string (Baker and Schroeder, 1967;Burnside, 1973;Burgess, 1982;Owaribe and Masuda, 1982). A recent study demonstrated that circumferential actin-myosin bundles can exhibit a clear sarcomeric organization in several epithelial tissues in vivo (Ebrahim et al, 2013). Myosin activity in these tissues reduces the distance between sarcomeric repeats, consistent with myosin motor activity pulling antiparallel F-actin arrays together, driving a pursestring-like contraction.…”
Section: Contractile Fibersmentioning
confidence: 99%
“…Superresolution structured illumination microscopy (SIM) analysis further shows paired NMIIB alignment between epicardial cells (Fig. 1B), reminiscent of NMII localization at epithelial cell-cell junctions (Ebrahim et al, 2013) and suggesting a role for NMIIB in regulating epicardial cell-cell adhesion.…”
Section: Abnormal Epicardium and Coronary Vessels In B − /B − Heartsmentioning
confidence: 99%